I'm sorry everybody,but this is Brazil. Armed robbery on the buses in Brazilian cities - Paes-Machado, Eduardo (The British journal of criminology, 2004)
This paper examines violent crimes on the public transport system in a large Brazilian city. The research included 191 interviews with workers, labour union officials, users, managers, and the police officers and the examination of 88 police records and 26 criminal investigations. Robberies are seen as interactive, relatively unexpected though common events. We interpreted bus robbery as a psychological power game generating financial loss, injuries and fatalities, racial tensions and harsh policing. We evaluated the efficiency of law and order measures taken to combat bus crime, including the excessive use of force by the police. The study concludes that improved policing social policies, targeting poor and black-mulatto youths, who make up most of the young offenders involved, should be implemented